910 PREVALENCE AND PROGNOSTIC IMPACT OF ANAEMIA IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION AND RECEIVING CANGRELOR: A SUBANALYSIS OF THE ICARUS REGISTRY. (15th December 2022) - Capolongo, Antonio; Gragnano, Feliceg; Benenati, Stefano; De Sio, Vincenzo; Scalamera, Riccardo; Bertero, Edoardo; Musumeci, Giuseppe; Annibali, Gianmarco; Campagnuolo, Salvatore; Galasso, Gennaro; Silverio, Angelo; Belllino, Michele; et al.
Abstract: Aims: To assess the clinical characteristics and compare in-hospital outcomes of patients with and without anaemia receiving cangrelor in the peri-percutaneous coronary intervention (PCI) phase. Methods: Consecutive patients treated with cangrelor in 7 Italian institutions were retrospectively enrolled in the ICARUS ("Intravenous CAngrelor in high-bleeding Risk patients Undergoing percutaneouS coronary intervention", NCT05505591) registry. According to the World Health Organization, anaemia was defined as haemoglobin (Hb) levels < 13 g/dL in men and < 12 g/dL in women; severe anaemia as an Hb value < 11 g/dL irrespective of sex. The primary endpoint was net adverse clinical events (NACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, definite or probable stent thrombosis and Bleeding Academic Research Consortium (BARC) 2, 3 or 5 bleeding, at 48 hours. Secondary endpoints were assessed at 48 hours. Major adverse cardiovascular events (MACE), defined as a composite of cardiovascular death, myocardial infarction, stroke and definite or probable stent thrombosis were also evaluated at discharge. Results: Out of 551 patients undergoing PCI with cangrelor between January 2019 and August 2022, 125 (23%) were anaemic. Mean age was 74±10 vs. 65±11 years in anaemic vs. non-anaemic patients (p<0.001). Baseline haemoglobin significantly differed between the two arms (12±1 vs. 15±1.2 mg/dl, p<0.001); severe anaemia occurred in the 24% of anaemic patients. Atrial fibrillation (20% vs. 6%, p<0.001) and chronic kidney disease (31% vs. 9%, p<0.001) were more frequent among anaemic individuals, in whom clopidogrel was more frequently administered after PCI (42% vs. 25%, p<0.001). At 48 hours, anaemic patients had higher rates of NACE (14% vs. 7%, p=0.019) and BARC 2, 3 or 5 bleeding (12% vs. 5%, p=0.013), whereas the rates of other 48-hour endpoints did not differ. At multivariable analysis, severe anaemia (odds ratio [OR] 1.12, 95% CI 1.02-1.24, p=0.015), acute coronary syndrome at presentation (OR 1.06, 95% CI 1.01-1.12, p=0.013), femoral access (OR 1.12, 95% CI 1.04-1.20, p=0.001) and cardiogenic shock (OR 1.27, 95% CI 1.13-1.44, p<0.001) independently predicted the occurrence of NACE. Complete in-hospital follow-up was available in 549 (99.6%) of patients, with MACE rates being not significantly different between anaemic and non-anaemic patients (2.4% vs. 2.8%, p= 0.593). Conclusions: Anaemia is a distinctive risk feature among patients receiving intravenous cangrelor in the peri-PCI phase. Anaemic patients experience higher incidence of adverse events at 48 hours, with severe anaemia being an independent predictor of NACE.